Development of Milk Product from Sacha Inchi (Plukenetia volubilis L.) - ตาเย๊ะ, นุชเนตร; สาแรหะ, ซูวีร่า; แวกาจิ, อาดีบะห์ (YRU Journal of Science and Technology, 2018)
The purposes of the research on development of milk Production from Sacha Inchi (Plukenetia volubilis L.) were to study the preparation of Shacha Inchi milk, Shacha inchi milk extraction, appropriate of sugar content and consumers’ acceptance of milk product. The study was focused on the product’s physical quality, chemical composition and sensory evaluation. were content of protein 23.60±0.12% fat 32.28±0.19% carbohydrate 22.12±0.09% total fiber 15.66±0.19% moisture content 3.67±0.08% and ash 2.67±0.03%. Proportion of Sacha Inchi bean and water at 1:3 (by dry Shacha Inchi weight) was used in extraction process and 8% of sugar content by weight are appropriated in shacha inchi milk production. The L* value, a* value and b* value were 78.79±0.58, -0.28±0.13 and 8.38±0.16, respectively The viscosity was 5.46 centipoint; Total soluble solid was 17.45±0.01 brix; and pH was 6.12±0.01 and total acid content in the form of lactic acid was 1.59±0.09 %. For chemical composition, it was found that, the milk content of 100 g., there were 290.00 kcal.Energy, 16.53±0.02 g., 23.59±0.01 g. and 2.60±0.01 of protein, fat and carbohydrate. respectively. The milk has total unsaturated fatty at 91.75% and it has the highest content of a- linolenic acid 42.82±0.13%, followed by linoleic acid 38.69±0.16% and oleic and 10.02±0.36%. respectively. A survey of 100 general consumers showed that 73% of consumers rated sacha inchi milk product at a moderate level like to most like.The results revealed that chemical composition of Sacha Inchi which grow in Songkhla, Thailand